Influência das janelas no conforto ambiental de uma câmara bioclimática de baixo custo - Rodrigues, Gabriel Celligoi (2020)
The extensive use of indoor environments today and the relationship between environmental comfort and energy efficiency is a prerogative for the buildings’ envelope improvement. Under these circumstances, in order to enable the experimental study related to environmental comfort, the Low-Cost Bioclimatic Chamber (CBBC) was built in 2018, at the Federal University of Technology from the State of Paraná (UTFPR). After its conclusion, several tests were developed in order to verify the suitability of the chamber to the conditions of environmental comfort, furthermore seeking to identify fragile points in its envelope. In exploratory activities, it was found that the windows are the points of greatest thermoacoustic fragility of the entire system. The main objective of this research is to analyze how windows influence environmental comfort inside CBBC, considering the climatic conditions of Curitiba/PR. To this end, the thermoacoustic impact of different windows was identified as well as their sealing capacity and the conditions of environmental comfort provided by the windows inside CBBC. With the improvement of the windows’ efficiency it is concluded that the conditions of environmental comfort in the CBBC modules will be improved, and it is imagined that the chamber will provide better results to the studies that will be developed in its installations.